ANALISIS TINDAK TUTUR ILOKUSI FILM PENDEK “NANTI KITA CERITA TENTANG HARI INI THE SERIES EPS 01” PADA KANAL YOUTUBE TOYOTAINDONESIA - Ade Dufadhol Ariyadi; Mahatma Krishna HP; Asep Purwo Yudi Utomo (Universitas Wijaya Kusuma Surabaya, 2021)
AbstractToday, films have become a means of communication and conveying ideas that are increasingly massive. However, the purpose of dialogue and communication in films is sometimes not understood by most ordinary people. Therefore, we analyzed the speech act (dialogue) of one of the short films entitled